2022
DOI: 10.3390/antiox11091661
|View full text |Cite
|
Sign up to set email alerts
|

Full Regression of Peyronie’s Disease Plaque Following Combined Antioxidant Treatment: A Three-Case Report

Abstract: Peyronie’s disease (PD) is a fibrotic disorder of the tunica albuginea of the penis. Conservative medical therapy includes oral and/or injective active substances. Until now, only two PD patients who recovered after medical treatment are described in the literature. This article describes three new cases of PD patients who achieved complete resorption of plaque following antioxidant treatment. Case Presentations: Case 1. The patient was a 34-year-old man, a smoker, with lateral-left penile curvature (40 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Even if the aim of this study was not the following, our results testified to the elimination of the plaque after antioxidant treatment, as other articles in the literature have already described [72][73][74][75].…”
Section: Discussionmentioning
confidence: 77%
“…Even if the aim of this study was not the following, our results testified to the elimination of the plaque after antioxidant treatment, as other articles in the literature have already described [72][73][74][75].…”
Section: Discussionmentioning
confidence: 77%
“…Recently, we published three case report articles, where we presented eight patients (in total) with PD whose plaque disappeared completely after multimodal antioxidant treatment [ 28 , 29 , 30 ]. There was no photographic documentation in these case reports.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Paulis et al published a case report of three cases that showed full plaque regression, curvature improvement, and resolution of pain with a combination of oral antioxidants and topical propolis crème in one case and with the addition of pentoxifylline injections in the other two cases. 97 The authors do not specify what phase of disease these patients were in but do report that full regression required between two and four years of therapy. Penile ultrasound was utilized to monitor plaque regression.…”
Section: Novel Therapies For Peyronie’s Diseasementioning
confidence: 99%